Design of Fuel Monitoring Application for Reservoir Tanks in Army Fuel Supply Point on Military Logistics Corps Based on Internet of Things - Rizky Safrizal Akbar; Fajar Kholid; Kasiyanto Kasiyanto; Dekki Widiatmoko; Afif Achmad (International Journal of Engineering and Computer Science Applications (IJECSA), 2024)
The Bekang Corps, a vital component of the Army responsible for logistics and transportation, plays a crucial role in maintaining the military's operational readiness and mobility. In the intricate landscape of military operations, the seamless integration of strategy, logistics, and tactics becomes imperative for success. Integrated logistical support, encompassing maintenance, supply, personnel, education, and training, and base facility support, serves as the backbone of effective military operations. However, the manual monitoring of underground fuel tanks at Storage and Supply Points (SPBT) presents challenges in terms of potential errors, time consumption, and significant efforts. The aim of this research is to address these issues by focusing on leveraging Internet of Things (IoT) technology to design and implement a monitoring application specifically tailored for the SPBT environment within the Army's Bekang Unit. This research method is aimed at providing a real-time solution for efficiently monitoring and managing fuel levels. By integrating the Float Level Switch sensor and NodeMCU ESP 8266 microcontroller, this research establishes a foundation in IoT. The Android application, developed using Android Studio, serves as the user interface, while Firebase functions as the real-time database, facilitating seamless communication and data exchange. The results of this research are the successful implementation of this IoT-based solution, which not only enhances the accuracy and responsiveness of fuel level monitoring but also contributes significantly to military operational efficiency. The anticipated significant contribution of the application includes the enhancement of military operational efficiency, the reduction of human error risks, and an increased sense of responsibility regarding fuel availability for operational needs.